The Impact of Internal Operational Constraints on Humanitarian Aid Efficiency - Ghosh, Robin (Journal of Social Science and Humanities, 2025)
The relevance of the study is due to the growing need for humanitarian and life - saving assistance. In this regard, this article is aimed at exploring the impact of internal restrictions on aid delivery on aid effectiveness in humanitarian crises. In this paper the infant mortality rate as a proxy to measure aid effectiveness is used. It operationalizes the dependent and independent variables, while accounting for and ruling out alternative explanations influencing causation. The paper also touches upon the definitions of humanitarianism and the humanitarian system. Then, it reviews the literature on the subject to draw analysis from existing scholarships and address the gaps to build on this study. The findings emphasize the necessity for further research on the relationship between infant mortality and access constraints in humanitarian settings. This article also explores the relationship between access constraints and aid efficiency in mitigating food insecurity, using economic stability, donor contributions, and health expenditure. Political factors, external influences, and limited data pose challenges to the research design. The study assumes well - designed humanitarian projects and examines data over recent years to assess the impact of aid delivery on reducing mortality rates. Lastly, the paper presents the results of the study and concludes by citing the significance of the research.